Neomyth and Deconstruction: the Courtly Narrative and its Transformation in John Updike’s «Brazil» - Gonchar-Khanjyan, Natalie (Bulletin of Yerevan University B: Philology, 2025)
This article examines John Updike’s «Brazil» (1994) as a postmodern transformation of the Tristan and Isolde myth within the framework of magical realism and postcolonial discourse. The study hypothesizes that Updike does not reproduce the canonical narrative, but deconstructs it, presenting courtly love as resistance to societal norms, racial hierarchy, and gender constraints. The aim is to analyze how the novel reconfigures key mythopoetic elements–archetypes, sacred objects, ritual, and liminal space–through narrative inversion and symbolic reinterpretation. Particular attention is given to onomastic symbolism, the theme of embodiment and initiation, and the replacement of medieval ethics with contemporary identity politics. The methodological approach combines hermeneutics, structuralism, and postcolonial theory, alongside tools from comparative mythology and literary semiotics. The article argues that «Brazil» functions as a neomyth – a syncretic philosophical parable where the miraculous emerges not from divine intervention but from the human capacity to transgress. In reimagining the legend through a poetic of hybridity and transformation, Updike’s novel challenges traditional conceptions of love, fate, and the heroic, revealing how myth adapts to modern cultural and historical contexts. Ջոն Ափդայքի «Բրազիլիա» (1994) վեպը դիտարկվում է որպես պոստմոդեռնիստական կերպափոխում Տրիստանի և Իզոլդայի մասին առասպելի՝ մոգական ռեալիզմի և հետգաղութային դիսկուրսի տեսանկյունից։ Հիպոթեզն այն է, որ Ափդայքը ոչ թե վերարտադրում է ավանդական նարատիվը, այլ ապամոնտաժում է այն՝ փոխակերպելով կուռտուազ սիրո մոտիվը հասարակական նորմերին, ռասայական և գենդերային հիերարխիային ընդդիմանալու ձևաչափի։ Հոդվածի նպատակը վերլուծելն է՝ ինչպես է վեպում վերաշերտավորվում առասպելի միֆոպոետիկ կառուցվածքը՝ արքետիպերի, սրբազան առարկաների, ծիսակարգի և սահմանագծային տարածքի վերիմաստավորման միջոցով։ Հատուկ ուշադրություն է դարձվում անունների խորհրդանշաբանությանը, մարմնավորման և նախաձեռնումի մոտիվներին, ինչպես նաև միջնադարյան բարոյագիտության փոխարինմանը ինքնության ժամանակակից խնդիրներով։ Մեթոդաբանությունը ներառում է հերմենևտիկ, կառուցվածաբան և հետգաղութային մոտեցումներ՝ համադրով միֆաբանական և գրական սեմիոտիկայի գործիքակազմով։ Աշխատությունը հանգում է այն եզրակացության, որ «Բրազիլիան» հանդես է գալիս որպես նեոմիֆ՝ փիլիսոփայական առակ այն սահմանների մասին, որտեղ մարդկայինը միաձուլվում է հրաշքին։ Ափդայքն իր հիբրիդային և փոխակերպվող պոետիկայով վերաիմաստավորում է սերը, ճակատագիրը և հերոսությունը՝ ցույց տալով, թե ինչպես է առասպելը վերափոխվում ժամանակակից մշակութային և պատմական համատեքստում։ В статье рассматривается роман Джона Апдайка «Бразилия» (1994) как постмодернистская трансформация мифа о Тристане и Изольде в контексте магического реализма и постколониального дискурса. Выдвигается гипотеза о том, что Апдайк не воспроизводит канонический сюжет, а деконструирует его, превращая куртуазную любовь в форму сопротивления социальным нормам, расовой и гендерной иерархии. Цель исследования – проанализировать, как в романе переосмысляются мифопоэтические элементы: архетипы, сакральные объекты, ритуал и пограничное пространство. Особое внимание уделяется ономастической символике, мотивам воплощения и инициации, а также замещению средневековой этики проблематикой идентичности. Методологическая основа включает герменевтический, структуралистский и постколониальный подходы в сочетании с элементами сравнительной мифокритики и литературной семиотики. Статья показывает, что «Бразилия» выступает как неомиф – философская притча о границах человеческого и чудесного, где мифологическое рождается не из сверхъестественного, а из способности героя к трансгрессии. Через поэтику гибридности и превращения Апдайк заново формулирует ключевые категории любви, судьбы и героизма, демонстрируя, как миф адаптируется к реалиям современной культуры.